A qualitative Study of Accessibility Health Services among Communities on Small Islands in Makassar City (Medico Legal Update, 2020)
This study aims to explore barriers to access in health services among small islands in Makassar City.This research is qualitative research through content analysis by observing phenomena that occur based onthe accessibility framework of Levesque, et.al. Data collection was carried out through in-depth interviewswith 8 key informants and 9 other informants (n = 17).This study found that geographical factors (distance, travel time, and transportation costs) were the mainconsiderations in utilizing primary health services in the small island communities around Makassar Citywhich were predominantly fishermen. The two closest islands (Barrang Caddi and Bone Tambung), haveenjoyed easy access and free service for Universal Health Coverage (UHC) achievements.It is different from the outer islands, especially Langkai and Lanjukang, although most of the residentsalready have National Health Insurance (NHI) they have difficulty using their cards due to geographicalconstraints. Moreover, fishermen often go fishing for days, becoming another obstacle in accessing qualityhealth facilities available in Makassar City.Various efforts have been made by the Makassar City Health Office to address the disparity in healthservices in the islands in Barrang Caddi, such as the use of sea ambulances, and regular visits. The marineambulance is only one ship on standby between two public health centers in another village office if there isan emergency patient who must be referred to a hospital in Makassar City.This disparity in access to health services triggers injustice among residents of the islands in the MakassarCity area. Very contractual with the slogan: “Makassar City of the World”.This study revealed a special transportation need in the form of a very simple capacity sea ambulance andmanaged by island community communities that are not reached by sea ambulances from the public healthcenter.